PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF DAN SELF- EFFICACY PADA MATERI TRIGONOMETRI SMA - Yana Royana; Hanifah Hanifah; Zamzaili Zamzaili; Saleh Haji (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study was to determine the effect of the problem-based learning (PBL) model on students' creative thinking abilities and self-efficacy. The type of research used is quasi-experimental. This research was conducted at senior high school Sukakarya Musi Rawas with a population of all class X students totaling 114 students. The sample was selected by simple random sampling technique with class X MIA 1 as the experimental class and class X MIA 3 as the control class with 30 students each. Data collection methods are observation, tests, interviews, and documentation. Data analysis used multivariate statistical tests analysis of variance. The results of the study show that: there is a significant effect of using the PBL model on students' creative thinking abilities. There is a significant influence of students' Self-Efficacy abilities using the PBL model on students' mathematical problem-solving abilities